Virtual reality-based exercises to improve balance and hand grip strength in patients with hemiparesis caused by an electrical burn: A randomized controlled study - Nabil Fiaad, Mohamed; Fouda, Bassem M; Fayed, Islam H; Ahmed, Radwa S; Elmasry, Haitham M (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
There are many complications after an electrical burn injury, including neuromuscular defects, paresis or paralysis, Gillian barre syndrome, transverse myelitis, or amyotrophic lateral sclerosis. The aim of this study was to investigate the effect of virtual reality-based exercises on balance and hand grip strength in post electrical burn-induced hemiparetic patients. A randomized control trial pre- and post-experimental design with intra-rater reliability and inter-rater agreement was undertaken. Thirty post-electrical burn-induced hemiparetic patients (19 males and 11 females, aged 15 to 25 years) were randomly allocated into two equal groups (group A and B). Group A (n = 15) received virtual reality-based exercise in addition to the conventional physical therapy program. Group B (n = 15) received conventional physical therapy program only. The treatment was applied 3 sessions per week for 12 consecutive weeks. Posture stability and hand grip strength were measured by the Biodex balance system and handheld dynamometer, respectively. Data was collected prior to the first treatment and at the end of the 12-week trial and all statistical calculations were done using the computer program IBM SPSS. A statistically significant increase in the overall stability index and the power of hand grip strength was observed in both groups after treatment (p < 0.05), especially in group A, which received VR - based exercise training. Thus, group A showed a greater improvement in postural stability and hand grip strength than group B (p < 0.05). Virtual reality-based exercises as well as conventional physical therapy program were effective in improving posture stability and hand grip strength in post electrical burn-induced hemiparetic patients.